Productivity loss due to polycystic ovary syndrome and its relationship to race, mental health and healthcare delivery indices - Heather Gibson Huddleston, M.D; Alexander Milani, M.D., M.B.A; Rachel Blank, M.B.A (Elsevier, 2024)
Objective: To study the impact of polycystic ovary syndrome (PCOS) on work-related impairments and explore relationships with race, mental health, and healthcare delivery indices. Design: A cross-sectional internet-based survey. Setting: North American women with PCOS between August 2022 and October 2022. Patients: Individuals with a self-reported diagnosis of PCOS. Intervention(s): Not applicable. Main Outcome Measures: The primary outcome was missed work because of PCOS. The secondary outcomes included leave from work, impacts on the quality of work, and feelings of being held back at work because of PCOS. Results: Of 1,105 respondents, 1,058 reported having PCOS diagnosed by a physician. Of this group, 50.4% reported missing work because of PCOS, 72% felt that PCOS impacted the quality of their work, and 51.5% felt held back at work by PCOS. Multivariate analyses revealed that missing work because of PCOS was independently associated with black race, lack of insurance, requiring multiple doctors for a PCOS diagnosis, needing ≥3 doctors for current care, decreased satisfaction with care, and symptoms of anxiety and depression. Conclusions: Polycystic ovary syndrome significantly impacts employment-related productivity. Factors such as race, mental health, and healthcare delivery appear to play a crucial role in the extent of this impact.